English-medium instruction from an English as a lingua franca perspective : exploring the higher education context - Murata, Kumiko, 1952- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2019)
"English is increasingly used as a lingua franca (ELF) in communicative situations the world over with the acceleration of globalisation. This is in line with the increased introduction of English-medium instruction (EMI) to higher education institutions in many parts of the world to further promote both students' and faculty's mobility to make them competitive and employable in the globalised world, and to make their institutions more attractive and reputable. EMI and ELF, however, are rarely explicitly investigated together despite the fact that the spread of EMI cannot be separated from that of ELF. This volume tackles the issue head on by focusing on EMI in higher education from an ELF perspective. The volume includes contributions by Asian, European, Middle Eastern, South American and Anglo-American scholars. It discusses language policies, attitudes and identities, analyses of classroom EMI practices, case studies and finally, pedagogical implications from an ELF perspective, incorporating also theoretical and empirical issues in conducting EMI courses/programmes. The volume will be of great interest and use, not only to those who are conducting research on ELF, EMI, CLIL, language policy and related fields, but also to classroom teachers and policy makers who are conducting and/or planning to start EMI courses/programmes in their institutions or countries all over the world"--
Exploring EMI in higher education from an ELF perspective: introduction / Kumiko Murata -- The internationalisation of higher education: but what about its lingua franca? / Jennifer Jenkins -- Intelligibility, mimicry and internationalization: localized practices in higher education, or can the global south speak? / Clarissa Menezes Jordão -- English-medium instruction at Swedish universities: developments over the past decade / Maria Kuteeva -- English-medium instruction in the Korean higher education context: from an English as a lingua franca perspective / Joo-Kyung Park -- English-medium instruction in contemporary japanese higher education: from an english as a lingua franca perspective / Masakzu Iino -- Classroom discourse in EMI: on the dynamics of multilingual practices / Ute Smit -- Enacting an ELF-informed English-medium instruction curriculum: an autoethnography / Patrick Ng -- Internationalisation and the growing demand for English in Japanese higher education undertaking doctoral study in English / Jaroslaw Kriukow and Nicola Galloway -- "English"-medium instruction in a Japanese university: exploring students and lecturers¿ voices from an ELF perspective / Mayu Konakahara, Kumiko Murata and Masakazu Iino -- Identity and sociopragmatic language use among East Asian ELF speakers: its implication for English-medium education / Yoko Nogami -- The role of English in the internationalisation of higher education: a case study of a Chinese university's education policy and practice / Ying Wang -- Designing CELFIL (content and ELF integrated learning) for EMI classes in higher education / Nobuyuki Hino -- Expanding ELF-informed EMI in expanding circle higher education: a case study of actual graduates' needs / James E. D'Angelo -- Beyond global English(es): university English program in transition / Masaki Oda -- Critical language testing and English lingua franca: how can one help the other? / Elana Shohamy.
Includes bibliographical references and index.
ENH
Parama Publishers
Keywords: English language -- Study and teaching (Higher) -- Foreign speakers; English language -- Study and teaching (Higher) -- Foreign countries; English language -- Globalization